Behavioral phenotyping identifies autism-like repetitive stereotypies in a Tsc2 haploinsufficient rat model - Antonia Ramme; Mirjam Zachow; Bettina Habelt; Iveta Vojtechova; Tomas Petrasek; Robert Waltereit; Nadine Bernhardt (Behavioral and Brain Functions)
Abstract Besides deficits in social communication and interaction, repetitive behavior patterns are core manifestations of autism spectrum disorder (ASD). Phenotypes are heterogeneous and can range from simple lower-order motor stereotypies to more complex higher-order cognitive inflexibility and fixated interests. Due to ASD’s multifaceted etiology, animal models are often generated from monogenic diseases associated with ASD, such as Tuberous Sclerosis Complex (TSC), and are expected to copy behavioral core deficits to increase the model´s translational value for ASD disease research and novel treatment development. The global haploinsufficient Tsc2 +/− Eker rat model has been shown to display ASD core symptoms in the social domain. However, the presence and extent of aberrant repetitive behavior patterns in the Eker rat remain to be investigated. Thus, the present study applied a set of behavioral tests to determine the repetitive behavioral profile in Tsc2 +/− Eker rats and used brain-region-specific neurotransmitter analysis to support findings on a molecular level. Tsc2 +/− animals demonstrated lower-order repetitive behavior in the form of excessive self-grooming and nestlet shredding under non-stressful conditions that co-occurred alongside social interaction deficits. However, no higher-order repetitive behavior was detected in Tsc2 +/− rats. Interestingly, Tsc2 +/− rats exhibited increased levels of homeostatic dopamine in the prefrontal cortex, supporting the link between aberrant cortical dopaminergic transmission and the appearance of lower-order repetitive phenotypes. Together, our results support the Tsc2 +/− Eker rat as a model of ASD-like behavior for further investigation of ASD-related development and neurobiology.